Ảnh hưởng của một số yếu tố đến kích thước hạt nano sắt được tổng hợp bằng phương pháp nổ - Nhiệm, Đàp Ngọc; Lịm, Dương Thị (Vietnam Journal of Chemistry, 2014)
The technology of wire explosion (WEE) has been used to produce nanopowder. A new concept was proposed to produce nanopowder, which is wire explosion in liquid media. Effects of the particles size of iron nanopowder by the WEE such as iron wire diameter, voltage and reaction times were investigated and discussed. The results showed that the distribution of average particle of iron nanopowder decreased when the voltage increased. The same experimental conditions while Fe wire diameter increased from 0.1 mm to 0.3 mm, then the distribution of the average particle size of iron increased from 0.1989 µm to 0.2241 µm. Keywords: Iron nanopowder, technology of wire explosion, liquid medium